The association between team behaviors and competitive anxiety among team-handball players: the mediating role of achievement goals - Wang, Xiaolin; Sun, Zhuo; Yuan, Lei; Dong, Depeng; Dong, Delong (Frontiers in Psychology, 2024)
Team sports athletes may encounter significant stress, leading to competitive anxiety. The anxiety levels can be influenced by team behaviors and achievement goals. This study aims to investigate the relationship between team behaviors (i.e., perceptions of controlling coaching behavior and team cohesion) and competitive anxiety, and to examine the mediation effects of achievement goals (i.e., task-oriented and ego-oriented) on the relationship. A total of 298 team-handball players were involved in the study, ages ranging from 16 to 24 years old (M = 18.44, SD = 3.09). A cross-sectional research design was adopted, and structural equation modeling was utilized to analyze path coefficients and mediating effects. Findings indicated that perceptions of controlling coaching behaviors had significant positive predictions for state and somatic anxiety (β = 0.22, 0.29) and negative predictions for self-confidence (β = −0.19). Team cohesion had significant negative predictions for state anxiety (β = −0.31) and positive predictions for self-confidence (β = 0.58). In addition, ego-oriented goals play a positive mediating role in the relationship between team behaviors and competitive anxiety (β = 0.03–0.35), while task-oriented goals play a negative mediating role in the relationship between team behaviors and competitive anxiety (β = −0.18 - −0.03). In conclusion, team behaviors have a significant relationship with competitive anxiety, with achievement goals playing a mediating role among them. Therefore, to alleviate team sports athletes’ competitive anxiety, it is recommended to reduce coach control behaviors, enhance team cohesion, and employ psychological training methods (e.g., mindfulness or meditation) to strengthen athletes’ task-oriented goals.